A linkage disequilibrium perspective on the genetic mosaic of speciation in two hybridizing Mediterranean white oaks - Goicoechea, P G (Heredity (Edinb), 2015)
We analyzed the genetic mosaic of speciation in two hybridizing Mediterranean white oaks from the Iberian Peninsula (Quercus faginea Lamb. and Quercus pyrenaica Willd.). The two species show ecological divergence in flowering phenology, leaf morphology and composition, and in their basic or acidic soil preferences. Ninety expressed sequence tag-simple sequence repeats (EST-SSRs) and eight nuclear SSRs were genotyped in 96 trees from each species. Genotyping was designed in two steps. First, we used 69 markers evenly distributed over the 12 linkage groups (LGs) of the oak linkage map to confirm the species genetic identity of the sampled genotypes, and searched for differentiation outliers. Then, we genotyped 29 additional markers from the chromosome bins containing the outliers and repeated the multilocus scans. We found one or two additional outliers within four saturated bins, thus confirming that outliers are organized into clusters. Linkage disequilibrium (LD) was extensive; even for loosely linked and for independent markers. Consequently, score tests for association between two-marker haplotypes and the ‘species trait' showed a broad genomic divergence, although substantial variation across the genome and within LGs was also observed. We discuss the influence of several confounding effects on neutrality tests and review the evolutionary processes leading to extensive LD. Finally, we examine how LD analyses within regions that contain outlier clusters and quantitative trait loci can help to identify regions of divergence and/or genomic hitchhiking in the light of predictions from ecological speciation theory.